Learning Lab - Collaborate, Learn and Adapt for better development outcomes - and Learning Lab (2013)
CLA is: a component of several missions' CDCSes. a conceptual framework for some principles and operational processes that can enable USAID to become a more effective learning organization and thereby a more effective development organization. an approach to facilitating local participation and capacity and promoting country-led development. For more information on CLA visit: